Inactive vaccine derived from velogenic strain of local Newcastle disease virus . - Darminto .; P Ronohardjo (Jurnal Ilmu Ternak dan Veteriner, 1996)
The objective of this research is to evaluate an application of an inactive Newcastle disease (ND) vaccine derived from velogenic strain of local Newcastle disease virus (NDV). In this research . the Ira strain of velogenic ND virus was grown in specific pathogen free (SPF) eggs and then was inactivated by formalin at a final concentration of 1 :1,000 at 4°C. The inactive antigen was then emulsified with an oil adjuvant or aluminium hydroxide gel before being administered for vaccination in layers and compared to a commercial inactive ND vaccine . Results indicated that application of these inactivated ND vaccines for booster vaccination following vaccination with an active lentogenic ND virus in pullets nearly producing eggs, resulted in high antibody titre which persisted for considerable long period of time and capable of protecting layers from sick of ND and from reducing egg production . Hence, it could be concluded that the inactivated vaccine emulsified in either oil-adjuvant (lanolin-paraffin) or aluminium hydroxide gel were considered to be highly immunogenic and capable of protecting layers from sick of  ND and from reducing egg production   Keywords : Newcastle disease, inactive vaccine, oil adjuvant . aluminium hydroxide, immunogenicity, protection